Archetypes for organizational safety - Marais, Karen; Saleh, Joseph H.; Leveson, Nancy G. (Safety science, 2006)
We propose an initial set of six system safety archetypes that model common dynamic organizational behaviours that often lead to accidents. The archetypes help clarify why safety-related decisions do not always result in the desired behaviour, and how independent decisions in different pans of the organization can combine to have a negative, and often unforeseen, impact on safety. Examples from the NASA manned space program and general industry are used to illustrate the archetypes. As accident analysis and investigation tools, the archetypes can be used to develop dynamic models that describe the systemic and organizational factors contributing to accidents. As risk analysis tools, the archetypes can be used to improve understanding of the ways that risk can arise in complex socio-technical systems.